Measuring the influence of dynastic politics in the MK Decision Number 90/PPU-XXI/2023 on democracy - Ermalinda, Jenny; Benu, Erlin Martina (Dynamics of Politics and Democracy, 2024)
Purpose: This study aims to analyze the impact of Constitutional Court Decision Number 90/PUU-XXI/2023 on the development of dynastic politics and its implications for democracy in Indonesia ahead of the 2024 General Election. Method: This research employs a qualitative descriptive method supported by normative legal analysis, drawing from constitutional provisions, court decisions, literature reviews, and survey data. This approach allows for a comprehensive examination of the intersection of law, politics, and democratic values. Results: The findings reveal that the Constitutional Court’s decision—permitting presidential or vice-presidential candidacy for individuals under 40 years of age if they have held an elected regional office—has intensified concerns regarding political dynasties. The public perceives this decision as favoring elite family interests, particularly the nomination of President Joko Widodo’s son, Kaesang Pangarep. This event reflects democratic backsliding and threatens the principle of equality before the law, creating imbalances in political competition and weakening public trust in the integrity of elections. Conclusion: Dynastic politics, legitimized through judicial decisions with potential conflicts of interest, pose a serious threat to Indonesia’s democracy. Although not illegal, dynastic politics undermines democratic norms, transparency, and equal opportunities in political participation. Limitations: This study is limited by its reliance on secondary data and the recent timeframe surrounding the 2024 election, which may restrict generalizability. Contributions: This study contributes to the discourse on democracy and legal politics by highlighting the urgent need for institutional reform, political party responsibility, and judicial impartiality to safeguard Indonesia’s democratic future.